Role of SENESCENCE-ASSOCIATED RECEPTOR-LIKE KINASE (SARK) in senescence regulation and developmental processes in Arabidopsis - Kurmanbayeva, A.; Soltabayeva, A.; Dauletova, N.; Dauletkyzy, A.; Mukhitkyzy, S.; Tleukhan, A.; Serik, S.; Tarlykov, P.; Rakhmetova, A.; Omondi, J.O.; Srivastava, S. (2024)
In light of increasing environmental stress, understanding the biological roles and molecular mechanisms of the genes implicated in senescence regulation and receptor perception could aid in the development of stress-tolerant crops. The precise function of SENESCENCE-ASSOCIATED RECEPTOR-LIKE KINASE (SARK) in senescence regulation and its potential involvement in signaling of stem cell development and early anther development in Arabidopsis plants remains ambiguous. The current study aimed to elucidate the involvement of SARK in senescence regulation and explored its potential as a target for enhancing plant stress tolerance. Over-expression (OE) lines of SARK, OESARK were generated in Arabidopsis. Evaluation of phenotypic appearance, chlorophyll levels in old leaves, and the expression of senescence-related proteins and transcripts did not reveal any changes in senescence symptoms compared to the wild-type plants (WT), suggesting that SARK might not act as a regulator of senescence. In addition, no disparities were observed in the growth of seedlings, juveniles, and adult stages, particularly in terms of biomass, rosette diameter, and flower structure in the OESARK line compared to the WT. The expression of genes such as BARELY ANY MERISTEM 2 (BAM2), NSP-interacting kinase 1 and 3 (NIK1, NIK3), and SOMATIC EMBRYOGENESIS RECEPTOR KINASE 1 (SERK1), which are known to interact with SARK in various organs and old leaves, was found to be modulated in OESARK lines. The altered expression of these genes involved in different developmental processes indicate its role in multiple pathways. Further study using suitable mutants could lead to discerning the specific roles of SARK.